Health and Economic Growth: Reconciling the Micro and Macro Evidence - David E. Bloom; David Canning; Rainer Kotschy; Klaus Prettner; Johannes Schünemann (Center for Economic Studies and ifo Institute (CESifo), 2022)
Economists use micro-based and macro-based approaches to assess the macroeconomic return to population health. The macro-based approach tends to yield estimates that are either negative and close to zero or positive and an order of magnitude larger than the range of estimates derived from the micro-based approach. This presents a micro-macro puzzle regarding the macroeconomic return to health. We reconcile the two approaches by controlling for the indirect effects of health, which macro-based approaches usually include but micro-based approaches deliberately omit when isolating the direct effect of health. Our results show that the macroeconomic return to health lies in the range of plausible microeconomic estimates, demonstrating that both approaches are in fact consistent with one another.
Keywords: I15; I25; J11; O11; O15; 330; productivity; population health; human capital; economic development